Gambaran pengetahuan remaja tentang diet sehat - Ade Tika Herawati; Manaf Manaf; Nadia Fauziawati Dewi (THE JOURNAL OF Mother and Child Health Concerns, 2022)
Background: Unhealthy diets that are often carried out by teenagers are irregular eating patterns, frequent consumption of fast food, use of diet drugs, laxatives, and binge-eating. An unhealthy diet can put you at risk of diarrhea, dehydration, fatigue all the time, nausea, headaches and constipation. In the long term unhealthy diet can cause osteoporosis, suffer from eating disorder behavior (such as anorexia nervosa, bulimia nervosa), cause anemia, diabetes mellitus or even dyspepsia. Data obtained from the Bandung Regency Health Profile (2020), regarding the incidence of dyspepsia in adolescents aged > 15 years in Bandung Regency is 41,818 cases. Purpose: This study aims to describe the knowledge of adolescents in Cimenyan Village, Cimenyan District, Bandung Regency. Methods: This type of research is descriptive quantitative. The population and sample in this study were 58 respondents. The sampling technique uses total sampling. Retrieval of data using questionnaires. Data analysis used in the study used univariate analysis. Results: The research shows that 5 respondents (8.6 percent) have good knowledge, 15 respondents (25.9 percent) have sufficient knowledge and 38 respondents (65.5 percent) have less knowledge. Conclusion: Most of the respondents have less knowledge. Suggestion: It is hoped that the Cimenyan Health Center will provide facilities in carrying out counseling on healthy diets for adolescents in RW 02 so that they can increase adolescent knowledge.   Keywords: Healthy diet; Knowledge; Teenager.   Pendahuluan: Diet tidak sehat yang sering dilakukan oleh remaja adalah ketidakteraturan pola makan, sering mengkonsumsi fast food, penggunaan obat diet, laxative, dan binge-eating. Diet yang tidak sehat dapat mengakibatkan risiko terkena diare, dehidrasi, lelah sepanjang waktu, mual, sakit kepala dan sembelit. Dalam jangka panjang diet tidak sehat dapat menyebabkan osteoporosis, menderita perilaku makan menyimpang (seperti anorexia nervosa, bulimia nervosa), menyebabkan anemia, diabetes mellitus atau bahkan dyspepsia. Data yang didapatkan dari Profil Kesehatan Kabupaten Bandung (2020), mengenai kejadian dispepsia pada remaja usia > 15 tahun di Kabupaten Bandung adalah sebesar 41.818  kasus. Tujuan:  Penelitian ini bertujuan untuk mengetahui gambaran pengetahuan remaja di Desa Cimenyan Kecamatan Cimenyan Kabupaten Bandung. Metode: Jenis penelitian ini adalah deskriptif kuantitatif. Populasi dan sampel pada penelitian ini sebanyak 58 responden. Teknik pengambilan sampel menggunakan total sampling. Pengambilan data menggunakan pengisian kuesioner. Analisa data yang digunakan dalam penelitian menggunakan analisa univariat. Hasil: Dari penelitian menunjukkan bahwa 5 responden (8,6 persen) memiliki pengetahuan baik, sebanyak 15 responden (25,9 persen) memiliki pengetahuan cukup dan sebanyak 38 responden (65,5 persen) memiliki pengetahuan kurang. Simpulan: Sebagian besar dari responden memiliki pengetahuan kurang. Saran: Diharapkan Puskesmas Cimenyan menyediakan sarana dalam melaksanakan penyuluhan mengenai diet sehat pada remaja di RW 02 agar dapat meningkatkan pengetahuan remaja.